Bycatch from Bottom Crab Gillnet Fishery in Pattani Province - Buatip, Somsak; Rittiboon, Kua; Saengkaew, Supaporn; Thongroy, Pimonrat; Jantarat, Sitthisak; Yeesin, Pun; Chavavongsa, Chavapot; Kanirae, Dehma (Burapha Science Journal, 2026)
The study on bycatch from bottom crab gillnet fishery in Pattani province, was conducted during December 2018 to November 2019 with four local landing sampling. This study found that on average 34.87% of total catches is blue swimming crab (Portunus pelagicus). Whereas bycatch is highly diverse of 252 species which are dominated by 3 group species of fish (75 species), shellfish (67 species) and crab (58 species). 98 species (38.89%) of bycatch are availability. The average discard ratio and discard rate for total catches are 1.85 and 0.65, respectively. There are 3.96 of diversity index, 0.72 of evenness Index and 72.41 of similarity Index. The frequency of species occurrence were found 69 species are rare, 62 species are uncommon, 51 species are moderately common, 29 species are common and 41 species are abundant.